Pemikiran Ahmad Tafsir tentang Manajemen Pembentuk Insan Kamil - A. Rusdiana (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2017)
Abstract: This article discusses Ahmad Tafsir's thought about the management of forming Insan Kamil, through a study of literature focused on the criteria of human kamil, its characteristics and its relation to the objectives of Islamic education. It is known that the general purpose of Islamic education is to strive for the development of human potential to achieve the perfection of insan kamil, people of faith, piety, and obedient worship to Allah SWT. The perfect Muslim is the man who has smart and intelligent mind, strong body, pious heart to Allah SWT, and good skill, is able to solve the problems scientifically and philosophically, possesses and develops science, philosophy, and heart that is capable of connecting with the supernatural. The eight domains above imply that the concept of insan kamil is very relevant with the goal of Islamic education, which equally wants to form human or learners who are smart, faithful and devoted. The discussion starts from Ahmad Tafsir's Biography and Works, Islamic Education according to Ahmad Tafsir and ending with Ahmad Tafsirâ€™s thought about Insan Kamil.Â Keywords : Faithful insan kamil, Knowledgeable, Giving charity